Nonlinear Frequency Response Analysis (NFRA) of Lithium-Ion Batteries. (10th September 2017) - Harting, Nina; Wolff, Nicolas; Röder, Fridolin; Krewer, Ulrike
Abstract: Electrochemical Impedance Spectroscopy (EIS) is the most commonly used technique for dynamic analysis of Lithium-ion batteries. EIS, however, limits analysis to linear contributions of the processes. For Lithium-ion batteries with their nonlinear electrochemistry and physics, dynamics are only analysed with regard to linear system behaviour and therefore some dynamic information is not used. Nonlinear Frequency Response Analysis (NFRA) extends dynamic analysis to consider also nonlinearities. Higher excitation amplitudes are applied and higher order frequency responses Y n are measured. The spectra show distinct higher harmonic responses with strong characteristic nonlinear behaviour. We investigate amplitude and temperature dependency of higher harmonic responses as well as the impact of ageing of Lithium-ion batteries with NFRA. By correlating NFRA and EIS, solid diffusion, reaction and ionic transport contributions at and in the SEI can be separated and identified. Thereby the method of NFRA is seen as an important additional dynamic analysis method for Lithium-ion batteries.